Erratum: Correction of Figure. Influence of Gas Pain, Post-operative Resilience, and Body Temperature Discomfort in Laparoscopic Myomectomy Patients after Thermotherapy - JeongAe Lee; MyoungHwa Jeon; EunJu Park; JinAh Lee; GonMyoung Ahn; SeungShin Lee; JiIn Kim (Korean Society of Women Health Nursing, 2019)
The authors found a language error in the published article. The authors replace the Figure 1.